The asymmetry effect of oil price changes on inflation, and the welfare implication for Ghana - Ayisi, R.K. (Emerald Publishing Limited, 2021)
Purpose – High inflation levels remain a challenge in macroeconomic stabilization policies among developing economies. Oil price is identified as an important driver of inflation. In the wake of high and unstable international oil prices, the question regarding the relationship between inflation and crude oil prices, and its implication for economic welfare has become a fundamental empirical issue. Design/methodology/approach – This question is explored by estimating a non-linear autoregressive distribution lags (NARDL) model of inflation-oil nexus that examined the asymmetric response of inflation to oil price changes. The study then derived the welfare implication of the asymmetric responses, with implications for the petroleum pricing regime in Ghana. Findings – The study found that inflation responds asymmetrically to oil prices in the long-run but not in the short-run. The welfare cost associated with the asymmetric response increases with increasing rate. Practical implications – The findings of this study have some implications for petroleum product pricing in Ghana. Recently, Ghana has moved from regulating petroleum prices to the automatic adjustment system. By this policy, petroleum prices change in tandem with the crude oil prices and exchange rates on the international market. Whiles this policy might be comparatively efficient, the evidence of asymmetric response of inflation to changes in oil prices raises some issues about the welfare effect of the policy. Originality/value – The paper contributes to the literature on the inflation-oil price nexus by investigating critical questions that remain puzzling. These questions include; Does inflation respond asymmetrically to the positive and negative shock of equal magnitude in oil prices? Does inflation response to the asymmetry changes in oil prices have any implications for the welfare of the country? Is the effect of oil price changes pernicious?
Research Article
Keywords: Asymmetric; NARDL; Inflation; Oil prices and welfare